HMGB1 and HMGB2 proteins up-regulate cellular expression of human topoisomerase IIalpha - Stros, Michal; Polanská, Eva; Struncová, Sona; Pospísilová, Sárka (Nucleic acids research, 2009)
Topoisomerase IIalpha (topo IIalpha) is a nuclear enzyme involved in several critical processes, including chromosome replication, segregation and recombination. Previously we have shown that chromosomal protein HMGB1 interacts with topo IIalpha, and stimulates its catalytic activity. Here we show the effect of HMGB1 on the activity of the human topo IIalpha gene promoter in different cell lines. We demonstrate that HMGB1, but not a mutant of HMGB1 incapable of DNA bending, up-regulates the activity of the topo IIalpha promoter in human cells that lack functional retinoblastoma protein pRb. Transient over-expression of pRb in pRb-negative Saos-2 cells inhibits the ability of HMGB1 to activate the topo IIalpha promoter. The involvement of HMGB1 and its close relative, HMGB2, in modulation of activity of the topo IIalpha gene is further supported by knock-down of HMGB1/2, as evidenced by significantly decreased levels of topo IIalpha mRNA and protein. Our experiments suggest a mechanism of up-regulation of cellular expression of topo IIalpha by HMGB1/2 in pRb-negative cells by modulation of binding of transcription factor NF-Y to the topo IIalpha promoter, and the results are discussed in the framework of previously observed pRb-inactivation, and increased levels of HMGB1/2 and topo IIalpha in tumors.
Keywords: upregulace; protein HMGB2; DNA Topoisomerases, Type II; retinoblastomový protein; DNA-Binding Proteins; Humans; Promoter Regions, Genetic; Up-Regulation; DNA vazebné proteiny; Aged; HMGB1 Protein; HMGB2 Protein; senioři; lidé; Antigens, Neoplasm; protein HMGB1; mutageneze; antigeny nádorové; DNA; Transcriptional Activation; CCAAT-Binding Factor; aktivace transkripce; DNA-topoisomerasy typu II; Male; Mutagenesis; nádorové buněčné linie; Cell Line, Tumor; faktor vázající CCAAT; mužské pohlaví; promotorové oblasti (genetika); Retinoblastoma Protein